Damsels, monsters, and superheroes: Exploring the metanarrative of sex trafficking - Heber, Anita (International review of victimology, 2024)
Sex trafficking narratives tend to follow the same storyline: a young, female victim is lured into sexual slavery by a foreign offender, and in the end, she is rescued by a Western hero. This article examines the sex trafficking narrative, and its accompanying characters in popular media, with a specific focus on the victim. It combines sex trafficking research with theories about folk tales and concepts of purity and the sacred. Empirically, the article explores the narratives of sex trafficking in six internationally influential films and books. The analysis creates an understanding of why one particular victim, and one metanarrative of sex trafficking, continue to dominate contemporary popular media. It traces the moralistic narrative continuities of sex trafficking, and creates an understanding of why we keep repeating this particular narrative, and why we seem to need it.